(untitled) (Innovaciones Educativas, 2022)
This work is a reflection on plagiarism in public universities in Costa Rica. Our research is based on a content analysis of the documentation regarding plagiarism regulations found through an online search on the websites of all five Costa Rican public universities: Universidad de Costa Rica, Tecnológico de Costa Rica, Universidad Nacional, Universidad Estatal a Distancia and Universidad Técnica Nacional. Plagiarism is a complex problem in higher education that demands actions to strengthen the penalization, detection, and prevention processes. According to the regulations, universities have established measures to regulate different forms of academic dishonesty, including academic plagiarism. However, the analysis shows that even though public universities include articles dealing with plagiarism within their regulations, there are important differences relating to its definition, the seriousness of the offense, and related sanctions. Ultimately, this work shows some of the challenges universities face in preventing plagiarism.